2008
DOI: 10.1007/s11199-008-9531-2
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Development, Values, Adaptation, and Discrimination in Acculturating Adolescents: The Case of Turk Heritage Youth Born and Living in Belgium

Abstract: This study addressed gender differences and similarities in acculturation, values, adaptation, and perceived discrimination among middle (14-17 years) and late (18-20 years) adolescents. Girls perceived less discrimination and showed better adaptation than did boys. All adolescents valued openness to change and self-transcendence similarly, but older adolescents attached greater importance to their heritage culture and conservatism. Overall, a larger gender gap in acculturation experiences emerged in late adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
49
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 56 publications
(61 reference statements)
3
49
1
1
Order By: Relevance
“…For instance, in their study on the acculturation style of the Turkish second generation in Europe, Groenewold, de Valk, and Van Ginneken (2014) found that higher levels of religiosity and exposure to discrimination are associated with higher preference for Turkish norms, values, and customs (IGP) and with lower preference for the norms of the majority population (NSP). Güngör and Bornstein (2009) found that indicators of cultural distance influence the acculturation of the Turkish second generation in Belgium. The study of Vedder, Sam, and Liebkind (2007) on the acculturation of the Turkish second generation in north-western Europe confirms this influence.…”
Section: Linkages Determinants and Expectationsmentioning
confidence: 99%
“…For instance, in their study on the acculturation style of the Turkish second generation in Europe, Groenewold, de Valk, and Van Ginneken (2014) found that higher levels of religiosity and exposure to discrimination are associated with higher preference for Turkish norms, values, and customs (IGP) and with lower preference for the norms of the majority population (NSP). Güngör and Bornstein (2009) found that indicators of cultural distance influence the acculturation of the Turkish second generation in Belgium. The study of Vedder, Sam, and Liebkind (2007) on the acculturation of the Turkish second generation in north-western Europe confirms this influence.…”
Section: Linkages Determinants and Expectationsmentioning
confidence: 99%
“…Perhaps they had less prestigious occupations or were unemployed before moving, and so have less room to fall on the occupational hierarchy. Alternatively, immigrant males may face greater hostility than immigrant females (Güngör and Bornstein 2009), the centrality of breadwinning to men's self-identity may make the slights more painful, or men may be further handicapped by the slower pace of their acculturation.…”
mentioning
confidence: 99%
“…Both boys and girls may, of course, be empowered by the relative fall in the father's status and by their more rapid integration into a culture that proscribes forms of behaviour (e.g., power assertive disciplinary strategies) that would have enhanced the fathers' authority in the home country (Este and Tachble 2009). Güngör and Bornstein (2009) reported that Turkish adolescent girls adjusted to life in Belgium more rapidly than their male compatriots, but it is unclear whether this gender difference reflected the boys' aversion to the implied loss of status when moving from a patriarchal to a more egalitarian culture. Interestingly, those researchers also found that older adolescents regarded their heritage culture more positively and held more conservative values than younger adolescents did, introducing an age based differential on top of the gender gap in acculturation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Internalizing the values of collectivistic cultures within the process of parenting, the expression of an individual's own needs is typically inhibited in deference to valuing the needs of others; subsequently, it is common to note more authoritarian and restraining parenting, with a greater expectation of obedience dependence and sociability; on the contrary, parents from individualistic cultures tend to value self-reliance, self-interest, and autonomy within the socialization process, thereby having greater parental expectations of exploration and independence with an authoritative style of parenting [56]. At the same time, it is vital to note that the restrictive and normative parenting in collectivistic cultures is not necessarily associated with parents being rejecting or lacking in warmth [57][58][59][60].…”
Section: Individualistic Vs Collectivistic Culturesmentioning
confidence: 99%